2017
DOI: 10.1111/jam.13500
|View full text |Cite
|
Sign up to set email alerts
|

Phage applications for improving food safety and infection control in Egypt

Abstract: The results suggest that phages could be effective treatments for pathogenic bacteria in food relevant contexts in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 50 publications
(55 reference statements)
1
27
0
Order By: Relevance
“…Our results suggested that phage cocktail is a suitable candidate for biological control of Salmonella in foods. Other researchers also showed that the phage cocktail could control pathogenic bacteria in foods, biofilms and food safety quality [88,89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that phage cocktail is a suitable candidate for biological control of Salmonella in foods. Other researchers also showed that the phage cocktail could control pathogenic bacteria in foods, biofilms and food safety quality [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Because the high stability of phage cocktail could reduce the growth rate of bacteria at that temperature [90,91]. It has been demonstrated that, using high concentrations of phages generally achieved high reduction rates of pathogens [74,88,92]. When high titers are applied, phages are capable to absorb to the bacterial cells causing lysis to the cytoplasmic membrane without replication [10,93], reported as a process known as "lysis from without" [94].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages represent an alternative treatment for the control of bacterial contamination in foods as well as the control of bacterial infections in man and animals due to their abilities to specifically target bacterial host cells and self-replicating nature (Jassim and Limoges 2014; Summers 2001; Taha et al 2018). Research has demonstrated the use of bacteriophages to reduce E. coli O157:H7 in the gastrointestinal tracts of mice (Tanji et al 2005) and sheep (Bach et al 2003; Raya et al 2011), and on the surface of the meat (El-Shibiny et al 2017; O’Flynn et al 2004). Studies also suggest phage application could decrease the mortality rate of poultry on infected farms (Xie et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have characterized a number of diverse lytic bacteriophages to K. pneumoniae belonging to different families and demonstrated their potential in vitro (Bogovazova et al, 1991 ; Kesik-Szeloch et al, 2013 ; Hoyles et al, 2015 ). Bacteriophage therapy is regarded as a simple, safe and highly effective alternative to counter the rising problems associated with multidrug resistant bacteria (Qadir, 2015 ; El-Shibiny et al, 2017 ). Here we evaluate the lytic activity of bacteriophage ZCKP1 isolated from an environmental freshwater source in Egypt against a MDR K. pneumoniae KP/01 isolated from the foot of a diabetic patient.…”
Section: Introductionmentioning
confidence: 99%